Greater omentum flap in the treatment of infant postoperative mediastinitis - Nárlei Amarante Pereira; Aloísio Ferreira da Silva Filho; José Carlos Ribeiro Resende Alves; Erick Horta Portugal; Marconi de Oliveira Ruas; Rebeca Paohwa Liu da Fonseca; Cláudio Azevedo Salles; Augusto César de Melo Almeida; Raíssa Lemos Ferreira da Silva (Revista Brasileira de Cirurgia Plástica)
INTRODUCTION: Postoperative mediastinitis is a serious condition that presents high mortality rates. The greater omentum flap has been used with good results in postoperative mediastinitis after cardiac surgery. The use of this approach has not been reported in infants probably because at this age, the greater omentum is membranous, not bulky, and has little amount of fatty tissue. METHOD: Between July 2010 and August 2014, four infants who presented with mediastinitis after a cardiac surgery via sternotomy were treated. The surgical treatment consisted of steel wire removal, debridement, and wound washing, followed by transposition of the entire greater omentum to the mediastinal cavity. Surgical treatment was performed in a single step. No rewiring of the sternum was performed. RESULTS: All four patients survived the treatment and were discharged from the intensive care unit without infection. CONCLUSIONS: Although membranous and not bulky, the use of a greater omentum flap proved to be an excellent approach in infant postoperative mediastinitis.